2022
DOI: 10.1101/2022.10.28.22281660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence, seroconversion, and seroreversion of infection-induced SARS-CoV-2 antibodies among a cohort of children and adolescents in Montreal, Canada

Abstract: Importance: Repeated serological testing for SARS-CoV-2 allows the monitoring of antibody dynamics in populations, including detecting infections that are missed by RT-PCR or antigen testing. Understanding the factors associated with seroconversion and seroreversion as well as the duration of infection-induced antibodies can also inform public health recommendations regarding disease prevention and mitigation efforts. Objective: To use serological testing to assess the prevalence, seroconversion, and serorever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…Differences in seroconversion rates were observed by age group. Consistent with other studies, we found that young children were more affected by Omicron's surge with an estimated 36% higher rate of seroconverting, which was not seen in pre‐Omicron rounds 4–6 . This may be explained by the high vaccine uptake in the older age groups.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Differences in seroconversion rates were observed by age group. Consistent with other studies, we found that young children were more affected by Omicron's surge with an estimated 36% higher rate of seroconverting, which was not seen in pre‐Omicron rounds 4–6 . This may be explained by the high vaccine uptake in the older age groups.…”
Section: Discussionsupporting
confidence: 90%
“…We found that having a parent self‐identify as a racial or ethnic minority was associated with a 44% higher rate of seroconverting during this period than children with white parents. This was also an important risk factor for seroconversion in EnCORE's earlier rounds and has been highlighted on multiple occasions since the beginning of the pandemic as a major risk factor of infection and infection severity 4,5,14 . Our results support that even in the context of Omicron‐enhanced contagiousness, health inequalities still play a key role in SARS‐CoV‐2 incidence.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations